CORRELATION OF MISCONCEPTIONS ON STUDENTS' NUMERACY ABILITY IN ANSWERING MATH PROBLEM SOLVING PROBLEMS AT SD NEGERI 57 BANDA ACEH - Jinan, Riadhil; Aswita, Dian; Suryawati, Indah (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2023)
Misconception or misconception refers to a concept that is not in accordance with the scientific understanding or understanding accepted by experts in the field. Misconceptions often occur in math lessons. The purpose of this study was to determine the correlation of misconceptions to students' numeracy ability in answering math problem solving problems in SD Negeri 57 Banda Aceh. The population and sample of this study were all grade IV students of SD Negeri 57 Banda Aceh consisting of one class with a total of 27 students. This study used a quantitative approach with the type of research used was pretest posttest correlation research. Data collection technique by giving multiple-choice test questions consisting of 5 questions with alternative answers a, b, c, and d related to the material of mathematical problem solving. The results showed that the correlation value obtained was 0.628 with a significant 0.000. It can be said to be significant (0.000) < of 0.05. The calculated t value (-8.718) < the table t value (0.000). The conclusion of the results of the study is that there is a correlation of misconceptions on the ability of numeracy in answering mathematical problem solving grade IV students of SD Negeri 57 Banda Aceh.